Impact of Management Commitment with Green Organization on Organizational Performance: A Mediated Model (Journal of Asian Development Studies, 2025)
Organizational performance is a major corporate challenge and organizations are becoming more and more dependent on digitalization to achieve performance. For better performance, organizations need digitalization and management commitment. This quantitative study was conducted to investigate the impact of management commitment with green organizations on organizational performance in the presence of digitalization as a mediator. Data was collected from service-oriented organizations and the I.T sector in Lahore, Punjab, Pakistan. For data analysis, the study used SmartPLS and Structural Equation Modeling (SEM) to determine the relationship between the variables. The structural model analysis focused on assessing the relationships between variables in the model. The theories of the Resource-Based View (RBV) and the Technology Acceptance Model (TAM) clarified data analysis, directed the research process, and offered a framework for understanding the phenomena. The study's findings show that management commitment with green practices improves organizational performance. Organizations that embrace digitalization and green practices have higher profitability and enhanced operational efficiency. The research's conclusions have important implications for practitioners. The research's conclusions have significant implications for practitioners. In order to successfully implement green practices, organizations must concentrate on developing a strong managerial commitment to sustainability.